English Speaking Fluency and Accuracy Among Informatics and Civil Engineering Students - Hasibuan, Derliana; Anggraini Harahap, Dian; Sambayu, Harry; Ginting, Datulina (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines fluency and accuracy in English speaking among Informatics and Civil Engineering students at Asahan University. Forty-five second-semester participants (25 Informatics, 20 Civil Engineering) completed structured speaking tasks and semi-structured interviews. Using the Complexity–Accuracy–Fluency (CAF) framework, performances were assessed for speech rate, pauses, grammatical control, and lexical appropriateness. Results show that communicative-oriented instruction enhanced fluency, producing smoother delivery and reduced hesitation, while grammar-focused instruction improved accuracy, yielding fewer errors and more precise lexical choices. Interviews revealed that communicative classes encouraged confidence and risk-taking, whereas grammar-focused classes increased metalinguistic awareness but reduced spontaneity. The findings highlight that fluency and accuracy are dynamically shaped by instructional emphasis. Balanced pedagogical approaches integrating meaning-focused interaction with attention to form are recommended to cultivate oral competence that is both communicatively effective and linguistically precise in Indonesian EFL contexts.This study examines fluency and accuracy in English speaking among Informatics and Civil Engineering students at Asahan University. Forty-five second-semester participants (25 Informatics, 20 Civil Engineering) completed structured speaking tasks and semi-structured interviews. Using the Complexity–Accuracy–Fluency (CAF) framework, performances were assessed for speech rate, pauses, grammatical control, and lexical appropriateness. Results show that communicative-oriented instruction enhanced fluency, producing smoother delivery and reduced hesitation, while grammar-focused instruction improved accuracy, yielding fewer errors and more precise lexical choices. Interviews revealed that communicative classes encouraged confidence and risk-taking, whereas grammar-focused classes increased metalinguistic awareness but reduced spontaneity. The findings highlight that fluency and accuracy are dynamically shaped by instructional emphasis. Balanced pedagogical approaches integrating meaning-focused interaction with attention to form are recommended to cultivate oral competence that is both communicatively effective and linguistically precise in Indonesian EFL contexts.Keywords: fluency, accuracy, English speaking, Informatics Engineering, Civil Engineering